Enhanced tensile and dynamic mechanical properties of thermoplastic natural rubber nanocomposites - Hassan, Noor Azlina; Haji Ahmad, Sahrim; Rasid, Rozaidi (Taylor & Francis, 2011)

(untitled)
The melt compounding technique was employed to prepare thermoplastic natural rubber (TPNR) nanocomposites. The maleic anhydride grafted polyethylene (MA-PE) as a coupling agent was used to improve the filler-matrix interfacial adhesion. TPNR were prepared in the ratio of (70:20:10) from linear low-density polyethylene (LLDPE), natural rubber (NR) and liquid natural rubber (LNR) as a compatibilizer between the matrix. The composites were prepared using the in-situ method at the optimum processing parameter at 140C with 100 rpm mixing speed and 12 minutes processing time. The results of the tensile test showed that the optimum of clay loading was obtained at 4 wt%. Dynamic mechanical analysis (DMA) was performed to investigate the thermomechanical properties of the composites. The results show that the addition of organoclay has improved the storage modulus (E0) and loss modulus (E00) of TPNR nanocomposites. The a transition peaks was also shifted to the higher temperature. However, nanocomposites with MA-PE demonstrated higher, E0 and E00 compared to TPNR nanocomposites without MA-PE. The TEM results show good clay dispersion with a combination of intercalated-exfoliated structure in the TPNR matrix.